Hubungan antara Dukungan Orang Tua dengan Adaptabilitas Karier pada Siswa SMA di Jakarta - Glory Angela; William Gunawan (Universitas Kristen Maranatha, 2021)
This study aimed to investigate the correlation between parental support and career adaptability among highschool students in Jakarta. This study hypothesized that there was a positive correlation between parental support and career adaptability among highschool students in DKI Jakarta. 195 senior high school students aged 15-18 years participated in this study derived from purposive sampling. This study was a quantitative approach used parental support scale and Career Adapt-Ability Scale (CAAS). The data was analyzed with Spearman Correlation. The result showed r= 0,257 (p = 0,001<0,05) which means there was a positive correlation between between parental support and career adaptability among highschool students in DKI Jakarta. Some suggestions through this research are to examine other variables that contribute more, see the contribution between variables and modify the measuring instrument according to the student's circumstances. Keywords: adolescent; career adaptability; parental support